Factors Influencing and Their Impact On Brand Evangelism - Widodo, Monica; Ginting, Ari Mulianta (Institute of Computer Science (IOCS), 2024)
This research aims to examine and understand whether interaction quality, physical environment quality, result quality, brand image, brand symbolism, and customer satisfaction influence and impact brand evangelism at Starbucks Jabodetabek. The study falls under the category of quantitative descriptive research. Data were collected from the target population consisting of individuals with Starbucks Cards, making purchases at Starbucks twice a week, have ever recommended Starbucks to friends or family, and residing in the Jabodetabek area. Data collection involved the distribution of questionnaires, with a total of 201 respondents participating in the study. Subsequently, the data were processed and analyzed using the Partial Least Square Structural Equation Modeling (PLS SEM) approach from Smartpls 3.0. Multiple regression analysis was employed in the data analysis. The research findings indicate that interaction quality, physical environment quality, result quality, brand image, brand symbolism, and customer satisfaction positively influence brand evangelism at Starbucks Jabodetabek. Therefore, it is recommended that Starbucks enhance customer satisfaction performance to increase brand evangelism in the Jabodetabek region.